Gut Microbiota and Dysbiosis in Alzheimer’s Disease: Implications for Pathogenesis and Treatment - Liu, Shan (Mol Neurobiol, 2020)
Understanding how gut flora influences gut-brain communications has been the subject of significant research over the past decade. The broadening of the term “microbiota-gut-brain axis” from “gut-brain axis” underscores a bidirectional communication system between the gut and the brain. The microbiota-gut-brain axis involves metabolic, endocrine, neural, and immune pathways which are crucial for the maintenance of brain homeostasis. Alterations in the composition of gut microbiota are associated with multiple neuropsychiatric disorders. Although a causal relationship between gut dysbiosis and neural dysfunction remains elusive, emerging evidence indicates that gut dysbiosis may promote amyloid-beta aggregation, neuroinflammation, oxidative stress, and insulin resistance in the pathogenesis of Alzheimer’s disease (AD). Illustration of the mechanisms underlying the regulation by gut microbiota may pave the way for developing novel therapeutic strategies for AD. In this narrative review, we provide an overview of gut microbiota and their dysregulation in the pathogenesis of AD. Novel insights into the modification of gut microbiota composition as a preventive or therapeutic approach for AD are highlighted.